Value Relevance of Accounting Information in Uncertain Economic Policy Context: Evidence from Tunisia - Hejer Khaldi; Feten Hamama (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the impact of domestic and international uncertainty shocks on the relationship between book value, earnings, and stock price? Motivation- We refer to the prior research on the value relevance of accounting information (Dunham & Grandstaff, 2021) which offers valuable insights into how the financial market interprets accounting information. However, there has been little emphasis on changes in value relevance over time and the influence of economic conditions on the value relevance of accounting information (El Ghoul et al., 2021; Barth, 2023). Idea- The study used the Ohlson's (1995) price model to investigate the effect of economic policy uncertainty on the value relevance of financial statement information in Tunisian firms. The dependent variable was Stock price (MV). The independent variables were Book Value of equity (BVS), Earning (EPS), and Economic Policy Uncertainty (EPU). Data- The study was conducted on a sample of 36 firms listed on the Tunis Stock Exchange (TSE) over 14 years (2008-2021). Tools- The models were estimated using the Generalized Least Squares (GLS) method. Findings- This research demonstrates that even in a highly uncertain economic environment, book value and earnings remain suitable for evaluating stock prices. Despite accounting information possibly losing its relevance, earnings seem to hold more significance than book value in stock market pricing. Contribution- This study contributes to the existing research on the relevance of accounting information by examining the impact of economic uncertainty in a developing country. We assess uncertain economy by using Baker et al. (2016) measure, which is a global measure. We have been able to find a significant decline in the value relevance of book value in an uncertain economy and to confirm the practical perspective of agency theory.
Keywords: C12; D81; G10; G18; M40; M41; 650; Value relevance; stock market price; book value of equity; earnings; economic uncertainty